Heidegger and post-colonial fascism. Issue 2 (4th March 2017) - Love, Jeff; Meng, Michael
Abstract : Alexander Dugin is considered a fringe figure in contemporary Russia. Yet, his writings exert considerable influence and develop a virulent nationalism that exploits the vocabulary of post-colonial resistance in an unaccustomed way. Dugin should not be ignored, and this article gives a brief account of Dugin's peculiar brand of post-colonial thinking by reference to its central source: Martin Heidegger. Specifically, the article examines how Dugin adapts the anti-metaphysical thinking of Heidegger's most radical work of the 1930s – a thinking that seeks to renew Western thought in an other beginning – to the context of modern Russia as it tries to free itself from Western (American) domination. Dugin aims at nothing less than the creation of a new Russian identity and destiny that will not only save Russia but also, in a nod to Heidegger, renew the Western tradition itself from the "outside." If Dugin's political project is ambitious, so is his interpretation of Heidegger which attempts to bring out the full radicality of Heidegger's thinking, both as philosophy and as politics.